Punctaria Latifolia as a New Source of Alginate: Structural Characteristics and Biological Activity - Martinez-Gomez, F (Springer Science and Business Media B.V., 2025)
Alginate production is estimated to be around 30,000 tonnes per year, coming from a limited number of macroalgae species. Therefore, to diversify the market and make it sustainable over time, it is important to find new species that produce alginate. In this study, physicochemical characteristics and biological activity of alginate obtained from Punctaria latifolia were evaluated. An alginate yield of 17% (w/w) with a weight-average molar mass of ≈ 303 KDa, a polydispersity index of 1.6 and a M/G ratio of 1.09 was obtained. FT-IR spectra confirmed that the extracted polysaccharide had the characteristic of alginates and each extracted fraction showed the typical bands of MG, MM and GG blocks. Rheological properties of 0.1 N NaCl aqueous solutions of P. latifolia alginate showed that viscous modulus is higher than elastic one, and they presented a good emulsifying capacity against different food-grade oils and benzene. Also, P. latifolia alginate had an antioxidant capacity of 1.24 ± 0.1 mg AAEq g −1 alginate and showed antitumor effect on tumoral MCF-7 cells at concentrations of 1000 and 2000 µg mL−1. On the other hand, P. latifolia alginate had no cytotoxic effects on non-tumor, osteoblastic (hFOB) and fibroblastic (NIH3T3) cell lines. © The Author(s), under exclusive licence to Springer Nature B.V. 2024.